Adenomatoid mesothelioma with intranuclear inclusion bodies: A case report with cytological and histological findings. Issue 5 (16th November 2012) - Kawai, Toshiaki; Kawashima, Katsuhiko; Serizawa, Hiromi; Miura, Hiroyuki; Kyeongil, Kim
<x xml:space="preserve">Abstract</x> We report a very unusual cytologic feature, intranuclear inclusion bodies, in mesothelioma of a predominantly adenomatoid type. The patient, a 57‐year‐old woman, was presented with dyspnea and right pleural effusion. Pleural aspiration cytology revealed many cohesive ball‐like clusters, with a tubular pattern, composed of small atypical cells displaying a high‐nuclear‐cytoplasmic ratio. They had a nuclear groove and irregular intranuclear inclusion bodies. Right lung partial resection with thoracoscopy revealed that a white tumor had proliferated along the pleural surface at S8. Histology revealed nodular tumor cells forming dilated structures mixed with small tubular or glandular structures similar to those seen in benign adenomatoid tumors. These tumor cells had invaded peripheral lung tissues. Such inclusion bodies have not been reported earlier in mesothelioma. On the basis of this observation, we propose that the adenomatoid type of malignant mesothelioma be added to the differential diagnosis of malignant effusions when tumor cells with nuclear grooves and intranuclear inclusions are found in pleural aspiration cytology. Diagn. Cytopathol. 2014;42:436‐440. © 2012 Wiley Periodicals, Inc.